Investigation Of Magnesium Doped Calcium Copper Titanate (Cacu3ti4o12) On Ca And Cu Site Prepared By Solid State Reaction Method - Rahman, Mohd Fariz Ab (2013)
In this research, the effect of magnesium (Mg) dopant on dielectric properties of CaCu3Ti4O12 (CCTO) was investigated. Undoped CCTO and Mg-doped CCTO on Ca and Cu site (Ca1-xMgxCu3Ti4O12 and CaCu3-xMgxTi4O12 have been prepared by solid state reaction method. Starting materials of CaCO3, CuO, TiO2 and MgO were wet milled for 1 hour by using three wetting agents which are acetone, deionized water and ethanol. XRD analysis on calcined powders shows the formation of CaCu3Ti4O12 (CCTO) phase with present of minor secondary phases (CuO and TiO2). Mixing process in deionized water gave better mixing and produces higher intensity of CCTO phase after calcined at 900°C for 12 hours. Compacted pellet was sintered at 1020°C, 1030°C and 1040°C for 10 hours. The sintering profile of 1030°C/10 hours was identified as an optimum parameter in the formation of single phase of CCTO with fine grain growth, high density and low porosity. MgO composition had been verified from 1 until 10 mole percent for Ca and Cu site of CCTO structure. SEM images show that the grain size becomes larger with increasing the concentration of dopant. Density and porosity of sintered samples were improved by dopant.